The effects of reinforced concrete shear wall on the earthquake behaviour of the buildings with various column sections - Tuncay Kap (Journal of Asian Architecture and Building Engineering, 2025)
The drifts in the buildings vary depending on the stiffness, height and elasticity modules of the load-bearing elements. In this study, a five-storey reinforced concrete building model was designed as an example by using five different column sections with 35 × 35, 40 × 40, 45 × 45, 50 × 50 and 55 × 55 cm square sections with reference to the 2018 earthquake code. C-30 concrete and S-420 steel were used in the designed building models, and the behaviours of these structures under the influence of earthquakes were analysed. Earthquake calculation was done via Mod superposition and Dynamic Analysis method. According to the Turkish earthquake regulations, reinforced concrete shear walls were added both “x” and “y” axis to the same building project as 2‰ percent of the total project area. In the analysis, when a shear wall is added to the building designed with 35 × 35 cm columns, the total load carrying capacity of the building has increased by approximately 42%. When the building was designed with 55 × 55 cm columns and shear walls, it was observed that the load bearing capacity increased by approximately 91%. In addition to using shear wall, total floor earthquake displacement was decreased about 9 times according to the references value 35 × 35 cm columns.